Introduction: fluid networks and hegemonic powers in the Western Indian Ocean - Walker, I.; Ramos, M. J.; Kaarsholm, P. (Fluid Networks and Hegemonic Powers in the Western Indian Ocean, 2017)
This is certainly not a comprehensive and final book on the intertwining relationship between African participation in the regional trading and cultural networks of the Indian Ocean and the hegemonic presence of world powers in the area. Its purpose is rather to contribute, with a few meaningful exemplary case-studies, to assert the need for further and more inclusive investigation. It touches upon questions that have been independently addressed by different regional and inter-regional research networks (African studies, Gulf studies, Indian Ocean studies, Southwest Asian studies, etc.). The role of the Indian Ocean in global security, the increasing involvement of India and China in the economies of contemporary African states and the cultural links that bind eastern Africa to the Indian Ocean littoral are both intricate and temporally deep. The editors of this book hope that it may serve as a useful tool to bridge the different social sciences and regional studies areas, and create a clearer awareness of the deep-rooted, and evolving, ties between Africa and the Indian Ocean.